Resistance-Trained Individuals Are Less Susceptible to Oxidative Damage after Eccentric Exercise. (17th July 2018) - Spanidis, Ypatios; Stagos, Dimitrios; Papanikolaou, Christina; Karatza, Konstantina; Theodosi, Andria; Veskoukis, Aristidis S.; Deli, Chariklia K.; Poulios, Athanasios; Koulocheri, Sofia D.; Jamurtas, Athanasios Z.; Haroutounian, Serkos A.; Kouretas, Demetrios
Abstract : It has been proposed that exercise-induced oxidative stress and adaptations are dependent on training status. In this study, we examined the effects of training background on free radical generation and adaptations after eccentric exercise. Forty volunteers were divided into two groups (trained and untrained) and were asked to perform eccentric exercise. Then, their blood samples were collected pre, 24, 48, and 72 hours postexercise. Biomarkers indicating oxidative damage and the antioxidant profiles of the participants were measured in plasma and erythrocyte lysate both spectrophotometrically and chromatographically. The results revealed that the untrained group depicted more severe oxidative damage (protein carbonyls, malondialdehyde), weaker antioxidant status (reduced glutathione, static and capacity oxidation-reduction potential), and weaker radical-scavenging activity (superoxide radical scavenging and reducing power) compared to the trained participants. Our findings show that trained individuals are less susceptible to oxidative damage and suggest that generalized nutritional recommendations regarding recovery after exercise should be avoided.